712 Safety and Efficacy of Omegaven in Preterm Neonates with Parenteral Nutrition Associated Liver Disease. (October 2012) - Booth, G; Havranek, T; Armbrecht, E; Revenis, M; Klein, C; Scavo, L
Abstract : Background: Omegaven, a fish oil derived parenteral lipid emulsion rich in omega-3 fatty acids, has been used in the United States under Investigational New Drug applications to treat parenteral nutrition associated liver disease (PNALD) in neonates. Aims: To evaluate the safety profile and changes in serum direct bilirubin levels in preterm neonates with moderate to severe PNALD treated with Omegaven. Methods: A prospective observational study of parenteral nutrition (PN) dependant neonates with consecutive serum direct bilirubin levels above 3 mg/dL, separated by a minimum of 7 days, who were expected to require PN for at least 3 more weeks were considered for Omegaven therapy. Eligible neonates were treated with Omegaven, as the only lipid infusion, at a maximum rate of 1 g/kg/day. Omegaven therapy was stopped once the serum direct bilirubin level was less than 1 mg/dL on consecutive weeks, or the patient tolerated adequate enteral nutrition to stop PN. The change in serum direct bilirubin was compared using the Wilcoxon signed-rank test. Results: 17 neonates were eligible for the analysis with a mean gestational age at birth of 26.6 weeks and mean birth weight of 911 g. Omegaven was administered for a median of 57 days. The neonates tolerated Omegaven well, without significant changes noted in the safety indicators (coagulation profile, platelet count, serum triglyceride, glucose, albumine). Serum direct bilirubin levels decreased significantly during the treatment course (p = 0.035). Conclusions: Significant decrease in serum direct bilirubin levels was observed in neonates with PNALD; omegaven was well tolerated.